Tingkat Pengetahuan Masyarakat RW 02 Desa Menang Kabupaten Ponorogo Terhadap Penggunaan Antibiotik - Rida Ludfi Aprinuha; Reni Ariastuti; Khotimatul Khusna (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
The use of antibiotics is important to note because antibiotics are a class of hard drugs. Resistance is a problem that arises due to inappropriate use of antibiotics. Knowledge of the use of antibiotics is an important factor in overcoming the problem of resistance. This study aims to determine the level of knowledge of the community in RW 02, Menang village, Ponorogo regency, based on the use of antibiotics. The research is descriptive research with a sampling technique, namely quota sampling. The research instrument used a questionnaire with validity and reliability tests. The sample is a respondent based on inclusion criteria with 90 respondents. The results show that the level of knowledge of respondents with good, sufficient, and poor knowledge is 10%, 74%, and 16%, respectively. The knowledge assessment used questionnaire indicators regarding the general description of antibiotics was 55%, knowledge based on how to obtain antibiotics was 59%, knowledge based on the rules for using antibiotics was 59%, knowledge regarding the side effects of antibiotics was 72%, and knowledge regarding managing antibiotics was 60%. The conclusion is the level of knowledge of the majority of the community in RW 02, Menang village, Ponorogo regency, regarding the use of antibiotics is classified as a sufficient level of knowledge.